Chemical treatment for recycling of amine/epoxy composites at atmospheric pressure. (July 2018) - Ma, Yijia; Nutt, Steven
Abstract: The use of fiber-reinforced composites poses significant environmental problems because most end-of-life composite waste is sent to landfills, and effective recycling technologies have drawn research attention. Our previous study demonstrated that chemical treatments at atmospheric pressure – depolymerization (benzyl alcohol/K3 PO4 at 200 °C) and acid digestion (acetic acid/H2 O2 at 110 °C) – were both effective for dissolution of amine-cured neat epoxy. In this paper, depolymerization and acid digestion were applied to amine/epoxy composites, including composites produced from lab-made and aerospace prepregs, and commercial composite waste. Findings indicated that acid digestion was more effective for highly crosslinked amine/epoxy composites than depolymerization. Furthermore, digestion occurred via reaction steps of oxygen atom transfer to the aniline groups and then bond cleavage, resulting in recovery of near-virgin quality fibers at faster dissolution rates and lower temperatures. The relationship between epoxy functionality, fiber bed architecture, fiber reinforcement, laminate thickness and matrix dissolution rate were investigated, and key parameters affecting the dissolution rate were identified. Data showed that the major rate-limiting factor for acid digestion was the diffusion rate, rather than the chemical reaction rate. Two strategies to enhance the diffusion rate – pre-treatment and mechanical shredding – were evaluated, and both were effective. Polymer matrices in pre-treated and shredded composites were homogeneously decomposed in 1 h. Highlights: Both depolymerization and acid digestion processes dissolve amine/epoxy matrices. Acid digestion is more effective for highly crosslinked amine/epoxy composites. Correlations between composite properties and dissolution rate are determined. Key factors affecting the recycling process are identified and modified. Two strategies to enhance the recycling rate are evaluated – both are effective.